Tenofovir–best hope for treatment of chronic hepatitis B infection? - Örmeci, Necati; Özbaş, Burak; Güner, Rahmet; Özkan, Hasan; Yalçı, Aysun; Çoban, Şahin; Dökmeci, Abdülkadir; Kalkan, Çağdaş; Akıncı, Hakan; Yüksel, Osman; et al. (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To evaluate the effectiveness of tenofovir in patients with chronic hepatitis B infection in a real life setting. Materials and Methods: We performed a retrospective analysis of data from 164 patients with chronic hepatitis B who were treated with Tenofovir. Eighty-six patients (52.4%) were naïve. Seventy-seven (46.9%) patients were previously treated with anti-viral drugs, including standard interferon (n=4), pegylated (PEG) interferon (n=14), standard interferon together with lamivudine (n=13), lamivudine alone (n=41), adefovir (n=2), lamivudine together with adefovir (n=1), and entecavir (n=2). Six patients (3.7%) had liver cirrhosis before treatment of tenofovir. Results: The patients who have hepatitis B viral DNA>104 copy/mL with chronic hepatitis B infection were included in the treatment of Tenofovir. Average follow up time was 30.31±14.33 months. HBV DNA negativity and alanine aminotransferase (ALT) normalization were 86.5% and 71.3%, respectively, at the last visit. Hepatitis B e-Antigen (HBeAg) seroconversion occurred in 11 (19.6%) out of 164 patients. During the follow-up period, 4 (2.4%) patients developed liver cirrhosis and in 5 (3%) patients hepatocellular carcinoma (HCC) occurred out of 164 patients. HBsAg seroconversion occurred in one patient (0.6%). Conclusion: Tenofovir can be used safely and successfully in those patients that were naive, experienced with immune modulators and/or antivirals, HBeAg-positive, and HBeAg-negative patients.